1999
DOI: 10.1084/jem.190.6.851
|View full text |Cite
|
Sign up to set email alerts
|

A Member of the Dendritic Cell Family That Enters B Cell Follicles and Stimulates Primary Antibody Responses Identified by a Mannose Receptor Fusion Protein

Abstract: Dendritic cells (DCs) are known to activate naive T cells to become effective helper cells. In addition, recent evidence suggests that DCs may influence naive B cells during the initial priming of antibody responses. In this study, using three-color confocal microscopy and three-dimensional immunohistograms, we have observed that in the first few days after a primary immunization, cells with dendritic morphology progressively localize within primary B cell follicles. These cells were identified by their abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
132
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(136 citation statements)
references
References 28 publications
4
132
0
Order By: Relevance
“…This would suggest that reconstruction of MTX-inhibited secondary humoral immune response requires interaction of LF with cells expressing neuraminic dependent receptors. The prime candidate for such a receptor is sialoadhesin, a sialic acid-binding receptor, found on murine tissue macrophages [10,14,28] and dendritic cells [4], and perhaps the CD22 marker on B cells that bears sequence similarity to sialoadhesin [20]. Nevertheless, the use of specific anti-sialoadhesin antibody, with no apparent crossreactivity with CD22, makes such a possibility very unlikely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would suggest that reconstruction of MTX-inhibited secondary humoral immune response requires interaction of LF with cells expressing neuraminic dependent receptors. The prime candidate for such a receptor is sialoadhesin, a sialic acid-binding receptor, found on murine tissue macrophages [10,14,28] and dendritic cells [4], and perhaps the CD22 marker on B cells that bears sequence similarity to sialoadhesin [20]. Nevertheless, the use of specific anti-sialoadhesin antibody, with no apparent crossreactivity with CD22, makes such a possibility very unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…To this mixture, dithiothreitol (DTT) was added to a final concentration of 10 mM and incubated at 37°C for 1 h. Iodoacetic acid in Tris base neutralized with NH 4 OH was added to a final concentration of 40 mM and incubated in the dark for 1 h. The sample was then bufferexchanged and concentrated with a Vivaspin 50,000 MWCO concentrator to roughly 1 mg/ml in 100 mM Tris-HCl, pH 7.4. The sample was subsequently split into four aliquots with each receiving 2.6 μg of trypsin in 10 mM HCl.…”
Section: Trypsin Peptide Mappingmentioning
confidence: 99%
“…BALB/c mice were subcutaneously immunized with OVA in alum, and 24 h later the draining LN were obtained for DC isolation as described elsewhere [35]. LN tissues were digested with 2.5 mg/ml of collagenase IV (Worthington, Freehold, NJ) and 1%/ml deoxyribonuclease (Sigma, St Louis, MO).…”
Section: DCmentioning
confidence: 99%
“…When tissue appeared to be completed digested, the enzyme reaction was stopped by the addition of ice-cold IMDM. After three washes using cold IMDM, digested tissue was submitted to discontinuous Percoll density gradient centrifugation and T cells were obtained by harvesting the 1.087-1.083 and 1.083-1.079 density interfaces [35]. Cell numbers and viability were assessed by trypan blue dye exclusion.…”
Section: Pancreas-infiltrating Leukocytesmentioning
confidence: 99%
“…MZ B cells in turn have been reported to transport blood-borne Ags into the Bcell FO in a C-dependent manner (22)(23)(24)(25). Alternatively, Ag can be transported into splenic and lymph node FO by a subset of macrophages/DCs identified by their ability to bind a fusion protein of the cysteine-rich domain of mannose receptor fused to the Fc portion of human IgG (CRFc + ) (26)(27)(28). We have recently shown that blood-borne VLPs are efficiently trapped in the MZ from where they are transported to FDCs in B-cell FO in a process dependent upon complement receptor expression on B cells as well as natural Ab (29).…”
mentioning
confidence: 99%